Experimental analysis on the impacts of soil deposition and bird droppings on the thermal performance of photovoltaic panels - Shaik, Saboor; Vigneshwaran, Pethurajan; Roy, Abin; Kontoleon, Karolos J.; Mazzeo, Domenico; Cuce, Erdem; Saleel, C Ahamed; Alwetaishi, Mamdooh; Khan, Sher Afghan; Gürel, Ali Etem; Ağbulut, Ümit (Elsevier, 2023)
Photovoltaic (PV) systems are capable of meeting the urgent demand for power production for both domestic and commercial purposes. PV systems possess serious drawbacks as their performance is heavily influenced by environmental variables like wind, radiation, shadow, dust, and soil accumulation. The current work examines the performance of solar PV panels in the presence of soil and dust at various tilt angles. A solar PV simulator was used, and experiments were conducted for a hot-dry climate location (Vellore, Tamil Nadu, India, 12.91◦ N, 79.1325◦ E), to evaluate the performance of solar PV panels under varying dust deposition. A total of seven different samples, such as black soil, desert soil, red soil, alluvial soil, laterite soil, coal dust, and bird droppings, were selected and dispersed over the surface of the PV panel at various weights of 10, 20, 30, 40, and 50 g. The physical characteristics of the dust samples have been emphasized as being essential in determining how effectively the PV panel functioned. Bird droppings were shown to have the most significant influence on PV panel efficiency because of their tendency to stick to the panel surface due to moisture content. Still, coal dust, independent of tilt angle, was found to have the least effect. Coal dust was determined to have the least impact on all soil types since it is quickly blown away and does not stick to the surface. Bird droppings accounted for about 46.42%–89.18% of the efficiency loss, which was determined to be high, whereas coal dust accounted